Phenotypic profle of monocyte-macrophage lineage cells as a function of respiratory epithelium status - A. A. Fedorov; N. A. Ermak; E. B. Topolnitskiy; N. A. Shefer; E. O. Rodionov; O. V. Pankova; N. V. Cherdyntseva; M. N. Stakheyeva (Сибирский онкологический журнал)
The mechanism of the relationship between pretumor changes in the bronchial respiratory epithelium and the risk of progression of non-small cell lung cancer (NSCLC) remains unclear. It has been suggested that the relationship between reactive changes in the bronchial mucosa and NSCLC progression may be caused by the functional status of monocytic-macrophage cells as important participants in infammation, which determines both the risk of premalignant changes in the epithelium and malignant progression. The purpose of the study was to investigate the phenotypic profle of peripheral blood monocytes and macrophages induced from monocytes in vitro depending on the state of respiratory epithelium in NSCLC patients. Material and Methods. The study included 39 patients with newly diagnosed NSCLC. Based on the morphological examination of small bronchi taken at the distance of 3–5 cm from the tumor, patients were divided into the following groups depending on the type of pretumor changes: no pretumor changes (n=6), isolated basal cell hyperplasia (BCH) (n=13), combination of BCH and squamous metaplasia (SM) (n=3), combination of unchanged epithelium and focal BCH (n=17). The phenotypic features of peripheral blood monocytes and in vitro-induced macrophages were assessed before treatment using fow cytometry. Results. The state of the respiratory epithelium in NSCLC patients prior to the start of anticancer treatment was associated with the phenotypic features of peripheral blood monocytes, but not with the profle of macrophages induced from them. Distortion of the response of induced macrophages to the polarizing stimuli was observed in NSCLC patients: the cultured cells responded to both M1 and M2 inducers (LPS and IL-4, respectively) with a phenotype shift to M2, while the CD206 marker expression varied depending on the presence and type of pretumor changes. Conclusion. The phenotypic profle of peripheral blood monocytes was associated with the state of the respiratory epithelium in NSCLC patients before anti-tumor treatment, but not with the phenotypic features of induced macrophages.